The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acssuschemeng.2c06309
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and Absolute Molecular Weight Determination of Organosolv Lignin and Its Fractions: Analysis by a Novel Acetone-Based SEC─MALS Method

Abstract: Accurate and reliable structural characterization of technical lignins is still challenging and inhibits industrial utilization as only poor understanding of structure–property relationship is available. Especially, molar mass analysis of technical lignins is of paramount interest; however, the usage of conventional size exclusion chromatography (SEC) and synthetic polymer standards as a consequence of inaccessible lignin standards is predominantly found in academia. This leads to a huge discrepancy in molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…This finding is particularly interesting for determining the efficiency of pyrolysis processes based on residual lignin fragments after the depolymerization process of RCF. The observations by Van Aelst et al correspond with other studies where lignin fractions exhibited a linear correlation between their size and polarity. This correlation is expected, considering the polyphenolic structure of lignin, where larger sizes result in a higher number of hydroxyl groups in the fraction …”
Section: Challenges and Perspectivessupporting
confidence: 75%
“…This finding is particularly interesting for determining the efficiency of pyrolysis processes based on residual lignin fragments after the depolymerization process of RCF. The observations by Van Aelst et al correspond with other studies where lignin fractions exhibited a linear correlation between their size and polarity. This correlation is expected, considering the polyphenolic structure of lignin, where larger sizes result in a higher number of hydroxyl groups in the fraction …”
Section: Challenges and Perspectivessupporting
confidence: 75%
“…Capturing more complex polymer distributions that cannot be completely characterized by a single average molar mass metric is still a challenge. This is specially important in the case of biobased polymers like lignin involving much more complex molar mass distributions . However, the future role of this type of biopolymeric materials is envisioned to become increasingly important in the context of biorefineries.…”
Section: Discussionmentioning
confidence: 99%
“…Lignin fractionation methods have been developed to produce lignin samples of reduced dispersity in distinct molar mass ranges. For acetone organosolv lignin, for example, fractionation could be achieved by consecutive solubilization in a variety of solvents or by stepwise precipitation by water dilution of the liquor. ,, The beech and birch wood lignin fractions thus obtained showed that a significant part of the lignin consists of large lignin fragments with weight-average molecular weights ( M w ) roughly between 2500 and 10 000 g/mol.…”
Section: Introductionmentioning
confidence: 99%